Qur’anic perspective on thinking and creativity: implication for education - Wan Yusoff, Wan Mazwati (2020)
Even though the teaching for thinking has been made compulsory in Malaysian education, but many Muslims believe that there is no reason in religion. This believe was made worse when some Muslim academicians and religious teachers have been actively disseminating the uselessness of reasoning in religion in social media and sermons. This study will explore and elucidate the functions, capabilities and limitations of thinking and creativity based on relevant Qur’anic verses. This is done to clarify the misconception and the compromising of the roles of aql or reason in Islam so as to answer the belief that reason has no place in Islam; and to accentuate the need and roles of creativity for sustainable future. This qualitative study will be using questioning and contemplative methods to critically analyze Qur’anic verses to reveal roles, capacities and boundaries of thinking. The findings from the analysis of the qur’anic verses will be evaluated based on the boundaries of the shari’ah and substantiated by prominent authorities in Islamic knowledge. Finally, the study will discuss implications for Islamic education.